1994
DOI: 10.1038/368667a0
|View full text |Cite
|
Sign up to set email alerts
|

Catch and move — cut or fuse

Abstract: Still almost unbelievable, but true: light exerts force. With these forces it is indeed possible to catch and move cells or small particles and microsurgically to process them without any mechanical contact. As if by magic, objects are moved via focused laser light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 37 publications
0
40
0
Order By: Relevance
“…Sections of colonic carcinoma tissue 5 m thick, fixed approximately 24 hours in phosphate-buffered saline buffered formalin (3.7%) and embedded in paraffin, were deparaffinized by incubating the slides in xylene for 2 ϫ 15 minutes, in 99.9% ethanol for 2 ϫ 10 minutes, in 96% ethanol for 2 ϫ 10 minutes, and in 70% ethanol for 2 ϫ 10 minutes and stained with H&E. Laser-microdissected tumor and normal muscle cell groups (n cell ϭ 30, 50, 100, ϳ250, ϳ500, and ϳ1000 each) 11 were lysed in alkaline buffer 13 or EL buffer as described above.…”
Section: Hande-stained Tissue Sectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sections of colonic carcinoma tissue 5 m thick, fixed approximately 24 hours in phosphate-buffered saline buffered formalin (3.7%) and embedded in paraffin, were deparaffinized by incubating the slides in xylene for 2 ϫ 15 minutes, in 99.9% ethanol for 2 ϫ 10 minutes, in 96% ethanol for 2 ϫ 10 minutes, and in 70% ethanol for 2 ϫ 10 minutes and stained with H&E. Laser-microdissected tumor and normal muscle cell groups (n cell ϭ 30, 50, 100, ϳ250, ϳ500, and ϳ1000 each) 11 were lysed in alkaline buffer 13 or EL buffer as described above.…”
Section: Hande-stained Tissue Sectionsmentioning
confidence: 99%
“…Positive cells were isolated from cytospots using a laser microdissector as previously described 11 and lysed in 10 l EL buffer (see the preceding subsection).…”
Section: Bone Marrow Aspiratementioning
confidence: 99%
See 1 more Smart Citation
“…Third, it is probably to some extent related to cell loss during the micromanipulation, because the final transfer of the picked cell to the PCR tube is not under visual control. Laser-assisted micromanipulation and automatic transfer directly into the PCR tube (Schutze and Clement-Sengewald 1994) might circumvent cell loss and mechanical DNA breakage. Finally, although we used PEP, it is impossible to amplify the target sequences every time because of significant locus-dependent variation in amplification efficiency (Sekizawa et al 1996b).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that differences in gene expression may account for distinct phenotypes in inbred strains. Although these transcriptome studies in the mouse have clearly shown that important and interesting biological information can be obtained by analysing heterogeneous tissues, there is no doubt that the implication of innovative technologies to reduce tissue complexity, such as laser-microdissection, will further improve the interpretation of gene expression data [68,69]. Whereas the microdissection technique is well established, the major challenge will be to improve the sensitivity of microarray hybridisations, for example, by establishing protocols for linear amplification of mRNA.…”
Section: The Potential Of Large Data Sets For Expression Analysismentioning
confidence: 99%